Ultrahigh‐Performance Liquid Chromatography–Mass Spectrometry Analysis of Carotenoid‐Derived Hormones and Apocarotenoids in Plants. Issue 2 (24th February 2022) - Mi, Jianing; Liew, Kit Xi; Al‐Babili, Salim
Abstract: Carotenoid oxidative cleavage products, apocarotenoids (APOs), are a class of important plant secondary metabolites, which include phytohormones abscisic acid (ABA) and strigolactones (SLs), and growth regulators and signaling molecules such as β‐cyclocitral, zaxinone, anchorene, β‐apo‐11‐carotenoids, and retinal. Qualitative and quantitative analysis of these bioactive compounds is crucial for understanding their metabolism and may also enable discovering further regulatory APOs. The state‐of‐the‐art mass spectrometry (MS) technology has advanced the detection of plant APOs; however, it is still challenging to perform an accurate analysis of the low‐level phytohormones ABA and SL and the structurally diverse APOs from complex plant matrices. Here, we describe ultrahigh‐performance liquid chromatography‐MS (UHPLC‐MS) methods to determine carotenoid‐derived hormones and APOs from plants by integrating ultrasound‐assisted extraction and solid‐phase extraction. These assays enable an accurate quantification of carotenoid‐derived hormones and APOs from plant tissues by using an UHPLC hybrid quadrupole‐Orbitrap mass spectrometer. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : UHPLC‐MS analysis of APOs from rice roots Support Protocol : Preparation of dried plant root powder Basic Protocol 2 : UHPLC‐MS analysis of SLs from rice roots Basic Protocol 3 : UHPLC‐MS analysis of ABA from rice roots